1965
DOI: 10.1042/bj0960449
|View full text |Cite
|
Sign up to set email alerts
|

The composition and physicochemical properties of hyaluronic acids prepared from ox synovial fluid and from a case of mesothelioma

Abstract: 1. Materials containing hyaluronic acid have been prepared by filtration (Ogston & Stanier, 1950) from ox synovial fluid and from a protein-rich human mesothelioma fluid. The ox material has been deproteinized by treatment with chloroform and pentanol and by gradient elution on DEAE-Sephadex; several fractions were obtained by the latter method. These materials can be stored in solution at -20 degrees without change of properties. The ox material contained 21% of protein; all other preparations contained less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
85
3
1

Year Published

1966
1966
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(94 citation statements)
references
References 52 publications
5
85
3
1
Order By: Relevance
“…However, contrary to the findings of Preston, Davies and Ogston (1965), only 50-60% of the total protein had come off the column by the time that small amounts of material containing uronic acid had begun to appear. The hyaluronic acid, which was recovered from the column by reversed flow (Preston, Davies, and Ogston 1965), still contained 13% of protein; Preston, Davies, and Ogston (1965) reported 6% of protein in hyaluronic acid recovered in this way. Table 1 shows the amino acid compositions of fractions 1, 2a (soluble), 2b (insoluble), and 3, 4, and 5.…”
Section: (C) Separation Of Protein From Ufr By Column Chromatographycontrasting
confidence: 48%
See 3 more Smart Citations
“…However, contrary to the findings of Preston, Davies and Ogston (1965), only 50-60% of the total protein had come off the column by the time that small amounts of material containing uronic acid had begun to appear. The hyaluronic acid, which was recovered from the column by reversed flow (Preston, Davies, and Ogston 1965), still contained 13% of protein; Preston, Davies, and Ogston (1965) reported 6% of protein in hyaluronic acid recovered in this way. Table 1 shows the amino acid compositions of fractions 1, 2a (soluble), 2b (insoluble), and 3, 4, and 5.…”
Section: (C) Separation Of Protein From Ufr By Column Chromatographycontrasting
confidence: 48%
“…Table 1 shows the amino acid compositions of fractions 1, 2a (soluble), 2b (insoluble), and 3, 4, and 5. Fractions 2a and 2b showed no marked differences from each other and resembled the protein analysed by Preston, Davies, and Ogston (1965). Fraction 1 differed significantly from them, particularly with respect to its contents of arginine, glutamic acid, glycine, and valine.…”
Section: (C) Separation Of Protein From Ufr By Column Chromatographymentioning
confidence: 83%
See 2 more Smart Citations
“…This was followed by extensive studies by light-scattering (Laurent & Gergely, 1955;Preston et al, 1965;Cleland & Wang, 1970), which all concluded that sodium hyaluronate adopted a solution conformation that was far more rigid than the random coil, although the possibility of domains of freely coiling chains was not excluded. The chain rigidity was attributed to inter-residue hydrogenbonding, and was further supported by evidence from periodate oxidation and n.m.r.…”
Section: Study Of Hyaluronic Acid Flexibility By Electric Birefringencementioning
confidence: 99%